ESTIMASI KARBON YANG TERKANDUNG PADA JENIS CEMARA GUNUNG (Casuarina junghuhniana Miq.) DI RESORT KONSERVASI WILAYAH TAMAN WISATA ALAM RUTENG WILAYAH I GOLO LUSANG - Elisabeth Sartika Hari; Lusia Sulo Marimpan; Maria M. E. Purnama (Wana Lestari, 2019)
Climate change due to global warming is an environmental issue related to forests which is now being explored in the future. Reducing the impact of climate change, efforts that can be done at this time are to reduce carbon emissions, increase carbon sequestration and maintain existing carbon stocks by managing forests to stay awake. The purpose of this study was to determine the estimation of the amount of carbon found in the type of Cemara Gunung (Casuarina junghuhniana Miq) at the Conservation Resort of the Golo Lusang Region I Nature Park in Ruteng. This study was limited to an area of ​​50 ha from the total area of ​​the Golo Lusang Region I, which was 8,742.83 Ha. Data retrieval is done by non destructive sampling method with sampling intensity of 5% of the total. Sampling in this study was carried out using the random sampling method. The amount of carbon reserves in each cemara gunung (Casuarina junghuhniana Miq) type is calculated by the allometric equation The total carbon content in the study location amounted to 246,592.66 tons / ha. For the tree phase that is equal to 245,308.1 tons / ha, the pole phase is 833.65 tons/ha of sapling phase of 450.92 tons/ha and seedling phase of 0 tons / ha. The highest percentage of carbon content is found in the stem (76%), twigs (16%) and leaves (8%).